2023
DOI: 10.1002/advs.202207621
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots Based Photoinduced Reactions: Advances and Perspective

Abstract: Seeking clean energy as an alternative to traditional fossil fuels is the inevitable choice to realize the sustainable development of the society. Photocatalytic technique is considered a promising energy conversion approach to store the abundant solar energy into other wieldy energy carriers like chemical energy. Carbon dots, as a class of fascinating carbon nanomaterials, have already become the hotspots in numerous photoelectric researching fields and particularly drawn keen interests as metal-free photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 208 publications
0
32
0
Order By: Relevance
“…For instance, a punctual comprehension of the synthetic mechanism yielding CDs should be achieved, and more rigorous methodologies to characterize the CDs properties must be developed. Filling this gap not only will allow for the synthesis of CDs with specific photocatalytic properties, but could also lead to the design and synthesis of novel nanomaterials for specific applications such as photodegradation of pollutants, [42] stereocontrolled photocatalysis, [16,25] and enzyme-mimicry. [43] Among these, enzyme-mimicking CDs, known as nanozymes, have recently gained increasing interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a punctual comprehension of the synthetic mechanism yielding CDs should be achieved, and more rigorous methodologies to characterize the CDs properties must be developed. Filling this gap not only will allow for the synthesis of CDs with specific photocatalytic properties, but could also lead to the design and synthesis of novel nanomaterials for specific applications such as photodegradation of pollutants, [42] stereocontrolled photocatalysis, [16,25] and enzyme-mimicry. [43] Among these, enzyme-mimicking CDs, known as nanozymes, have recently gained increasing interest.…”
Section: Discussionmentioning
confidence: 99%
“…[13b] Metal-doped CDs are also reported, mainly derived from organometallic complexes or metallic salts. [25][26] In addition, some organic solvents, such as formamide, can as well act as dopants, since during the synthesis is probable that they decompose and their by-products become incorporated into the CD structure. [27] The optical properties of these nanoparticles are primarily investigated by UV-Vis spectroscopy.…”
Section: Synthesis Purification and Characterization Of Photoactive Cdsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDs defined as 0D, discrete, quasi-spherical nanoparticles with a characteristic size less than 10 nm, were chiefly composed of sp 2 hybrid conjugated carbon as the core and a shell of functional groups (e.g., N-H, -OH, -COOH, CQN, C-O) or polymers. [1][2][3][4] The fluorescence (FL) of CDs is one of their most appealing characteristics, which allowed fortuitous discovery of CDs in 2004, 5 during the process of electrophoretic purification of single-walled carbon nanotubes (SWCNTs), and further found that these different fractions of colorful fluorescent materials are composed of different size-dependent components. However, it was not until 2006 that the term ''carbon quantum dots'' was formally defined by Sun et al 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (CDs) are carbon-based nanomaterials that have excellent optical properties, high chemical stability, good biocompatibility, and low toxicity; hence, they have broad application prospects in biological imaging, , sensing, drug delivery, , and photocatalysis. , In this way, CDs have attracted increasing attention of researchers worldwide. , The methods for the preparation of CDs include arc discharge, , laser ablation, electrochemical oxidation, chemical oxidation, microwave-assisted, and hydrothermal ,, methods. Among them, the hydrothermal method is simple and eco-friendly and does not require a complicated technology or special equipment. , Eco-friendly carbon sources (eggs, banana peel, papaya seeds, milk, , and leaves) are widely used for the preparation of CDs . Thus far, the application of CDs mainly in ion sensing and the use of pH-sensitive CDs have been reported rarely …”
Section: Introductionmentioning
confidence: 99%